Scalable and sustainable synthesis of carbon dots from biomass as efficient friction modifiers for polyethylene glycol synthetic oil - Mou, Zihao (2022)
Carbon dots (CDs) have lately inspired extensive interest in tribology, especially in the field of friction modifiers. However, it remains an enormous challenge to obtain satisfactory compatibility between CDs and base oils without laborious and tedious chemical modifications. In this work, for the first time, we reported a scalable and sustainable synthesis of CDs from easily and cheaply available biomass via a one-pot solvothermal route, which used ethanol as the renewable reaction medium and H2O2 as the clean oxidant. Typically, ginkgo leaves acting as the precursors were converted into CDs with an ultrahigh yield of 85.3%. As expected, the ginkgo leaf-derived CDs, abbreviated as GCDs, displayed excellent dispersibility, durable stability, and attractive fluorescence-emission behavior in PEG200. The as-prepared GCDs as additives for PEG200 exhibited remarkable lubricity, favorable load-carrying ability, and long operating life under boundary lubrication. Particularly, the antiwear and friction-reducing performances of PEG200 were promoted by 70.5% and 34.7%, respectively, when only 0.20 wt % of GCDs was blended. Confirmed by the tribological investigations and surface detection of wear tracks, the essential lubrication mechanism of GCDs was chiefly associated with the generation of GCD-inserted tribochemical films with a thickness of about 80 nm and their nanolubrication functions, that is, the synergistic effects of surface organic moieties and carbonaceous cores. This study establishes a technically simple, feasible, versatile, cost-effective, and green methodology to produce CD-based friction modifiers toward PEG synthetic base oils for tribological applications.